Mechanisms of Slower Nitric Oxide Uptake by Red Blood Cells and Other Hemoglobin-containing Vesicles - Azarov, Ivan (American Society for Biochemistry and Molecular Biology, 2011)
Nitric oxide (NO) acts as a smooth muscle relaxation factor and plays a crucial role in maintaining vascular homeostasis. NO is scavenged rapidly by hemoglobin (Hb). However, under normal physiological conditions, the encapsulation of Hb inside red blood cells (RBCs) significantly retards NO scavenging, permitting NO to reach the smooth muscle. The rate-limiting factors (diffusion of NO to the RBC surface, through the RBC membrane or inside of the RBC) responsible for this retardation have been the subject of much debate. Knowing the relative contribution of each of these factors is important for several reasons including optimization of the development of blood substitutes where Hb is contained within phospholipid vesicles. We have thus performed experiments of NO uptake by erythrocytes and microparticles derived from erythrocytes and conducted simulations of these data as well as that of others. We have included extracellular diffusion (that is, diffusion of the NO to the membrane) and membrane permeability, in addition to intracellular diffusion of NO, in our computational models. We find that all these mechanisms may modulate NO uptake by membrane-encapsulated Hb and that extracellular diffusion is the main rate-limiting factor for phospholipid vesicles and erythrocytes. In the case of red cell microparticles, we find a major role for membrane permeability. These results are consistent with prior studies indicating that extracellular diffusion of several gas ligands is also rate-limiting for erythrocytes, with some contribution of a low membrane permeability.